2016
DOI: 10.1111/tops.12206
|View full text |Cite
|
Sign up to set email alerts
|

Missing the Party: Political Categorization and Reasoning in the Absence of Party Label Cues

Abstract: This research addressed theoretical approaches in political science arguing that the American electorate is either poorly informed or dependent on party label cues, by assessing performance on political judgment tasks when party label information is missing. The research materials were created from the results of a national opinion survey held during a national election. The experiments themselves were run on nationally representative samples of adults, identified from another national electoral survey. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…As part of this larger research program, here we present collaborative research involving data collection from seven democracies featuring two‐ and multiparty systems: Australia, Canada, England, Hungary, Northern Ireland, the United States, and Scotland. As found in Heit and Nicholson (), we found that participants perceived politicians on the left and right as opposites. However, this pattern was not only found for parties on opposite sides of the ideological continuum in two‐party and multiparty systems, but here we report similar findings for parties on the same side of the ideological divide in multiparty systems.…”
Section: Party Distinctivenesssupporting
confidence: 85%
See 4 more Smart Citations
“…As part of this larger research program, here we present collaborative research involving data collection from seven democracies featuring two‐ and multiparty systems: Australia, Canada, England, Hungary, Northern Ireland, the United States, and Scotland. As found in Heit and Nicholson (), we found that participants perceived politicians on the left and right as opposites. However, this pattern was not only found for parties on opposite sides of the ideological continuum in two‐party and multiparty systems, but here we report similar findings for parties on the same side of the ideological divide in multiparty systems.…”
Section: Party Distinctivenesssupporting
confidence: 85%
“…The studies featured here advance a program of research (Heit & Nicholson, ; Nicholson, Coe, Martinsson, & Heit, ) that to now has focused on the role of party categorization in the American political system, a textbook example of a two‐party system. As part of this larger research program, here we present collaborative research involving data collection from seven democracies featuring two‐ and multiparty systems: Australia, Canada, England, Hungary, Northern Ireland, the United States, and Scotland.…”
Section: Party Distinctivenessmentioning
confidence: 99%
See 3 more Smart Citations